2020
DOI: 10.3390/cells9030697
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Inositides and Inositide-Dependent Signaling Pathways in Myelodysplastic Syndromes

Abstract: Myelodysplastic syndromes (MDS) are a heterogeneous group of hematological malignancies characterized by peripheral blood cytopenia and abnormal myeloproliferation, as well as a variable risk of evolution into acute myeloid leukemia (AML). The nucleus is a highly organized organelle with several distinct domains where nuclear inositides localize to mediate essential cellular events. Nuclear inositides play a critical role in the modulation of erythropoiesis or myelopoiesis. Here, we briefly review the nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 124 publications
0
11
0
Order By: Relevance
“…Furthermore, RhoA [55] and the RAS family of small GTPases, (RAS, RAS-related protein (Rap1) and Rap2B) [29,56] are able to activate PLCε through direct binding to the various domains of PLCε (Figure 2c). PLCε localizes within different cellular sub-compartments following its binding to Rap1 and RAS [29] or different cellular stimulations [37]: in perinuclear space [29,57], cytoplasm, and plasma membrane [29]. The ability of PLCε to be activated via several stimuli and its distribution across several cellular sub-compartments makes it one of the most complex signaling hubs.…”
Section: Plcδmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, RhoA [55] and the RAS family of small GTPases, (RAS, RAS-related protein (Rap1) and Rap2B) [29,56] are able to activate PLCε through direct binding to the various domains of PLCε (Figure 2c). PLCε localizes within different cellular sub-compartments following its binding to Rap1 and RAS [29] or different cellular stimulations [37]: in perinuclear space [29,57], cytoplasm, and plasma membrane [29]. The ability of PLCε to be activated via several stimuli and its distribution across several cellular sub-compartments makes it one of the most complex signaling hubs.…”
Section: Plcδmentioning
confidence: 99%
“…CAL-101 or idelalisib which is an approved PI3K inhibitor induces elevated cell death in chronic lymphocytic leukemia [82]. Interestingly, alterations in both PLCβ1 and PI3K/Akt/mTOR pathways have been associated with myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML) [57,83,84]. MDS are a group of hematological diseases characterized by impairment in cell differentiation and proliferation [79,85].…”
Section: Plcs In Cancer Cell Proliferation Survival and Tumor Growthmentioning
confidence: 99%
“…In hematopoiesis, and particularly in MDS, PLCβ1 is associated with both myelopoiesis and erythropoiesis, although with opposite effects [ 54 , 55 , 56 ].…”
Section: Targeting Inositide-dependent Signal Transduction Pathwaymentioning
confidence: 99%
“…Moreover, DGKs θ and ζ are found at the plasma membrane upon activation of some G protein-coupled receptors (Table 1) [73,74]. Several studies showed that the nuclear inositide signaling is involved in regulating essential cellular processes, such as cell cycle and differentiation [75][76][77][78], while it is also implicated in several pathologies, including myelodysplastic syndromes, brain diseases, and cancer [79][80][81][82]. Interestingly, DGKs, which have been discovered in nearly all cell compartments, were also found in the nucleus.…”
Section: Cellular Localization and Distribution Of Dgksmentioning
confidence: 99%